Aerobic catabolism of phenylacetic acid in Pseudomonas putida U: biochemical characterization of a specific phenylacetic acid transport system and formal demonstration that phenylacetyl-coenzyme A is a catabolic intermediate. - Schleissner, C (1994)
The phenylacetic acid transport system (PATS) of Pseudomonas putida U was studied after this bacterium was cultured in a chemically defined medium containing phenylacetic acid (PA) as the sole carbon source. Kinetic measurement was carried out, in vivo, at 30 degrees C in 50 mM phosphate buffer (pH 7.0). Under these conditions, the uptake rate was linear for at least 3 min and the value of Km was 13 microM. The PATS is an active transport system that is strongly inhibited by 2,4-dinitrophenol, 4-nitrophenol (100%), KCN (97%), 2-nitrophenol (90%), or NaN3 (80%) added at a 1 mM final concentration (each). Glucose or D-lactate (10 mM each) increases the PATS in starved cells (140%), whereas arsenate (20 mM), NaF, or N,N'-dicyclohexylcarbodiimide (1 mM) did not cause any effect. Furthermore, the PATS is insensitive to osmotic shock. These data strongly suggest that the energy for the PATS is derived only from an electron transport system which causes an energy-rich membrane state. The thiol-containing compounds mercaptoethanol, glutathione, and dithiothreitol have no significant effect on the PATS, whereas thiol-modifying reagents such as N-ethylmaleimide and iodoacetate strongly inhibit uptake (100 and 93%, respectively). Molecular analogs of PA with a substitution (i) on the ring or (ii) on the acetyl moiety or those containing (iii) a different ring but keeping the acetyl moiety constant inhibit uptake to different extents. None of the compounds tested significantly increase the PA uptake rate except adipic acid, which greatly stimulates it (163%). The PATS is induced by PA and also, gratuitously, by some phenyl derivatives containing an even number of carbon atoms on the aliphatic moiety (4-phenyl-butyric, 6-phenylhexanoic, and 8-phenyloctanoic acids). However, similar compounds with an odd number of carbon atoms (benzoic, 3-phenylpropionic, 5-phenylvaleric, 7-phenylheptanoic, and 9-phenylnonanoic acids) as well as many other PA derivatives do not induce the system, suggesting that the true inducer molecule is phenylacetyl-coenzyme A (PA-CoA). Furthermore, after P. putida U is cultured in the same medium containing other carbon sources (glucose or octanoic, benzoic, or 4-hydroxyphenylacetic acid) in the place of PA, the PATS and PA-CoA are not detected; neither the PATS nor PA-CoA is found in cases in which mutants (PA- and PCL-) lacking the enzyme which catalyzed the initial step of the PA degradation (phenylacetyl-CoA ligase) are used. PA-CoA has been extracted from bacteria and identified as a true PA catabolite by high-performance liquid chromatography and also enzymatically with pure acyl-CoA:6-aminopenicillanic acid acyltransferase from Penicillium chrysogenum.